Optimization of energy-saving distillation system of absorption heat pump based on intermediate heat exchange. (August 2022) - Li, Yan; Ding, Yixiao; Cao, Manman
Highlights: An absorption heat pumps distillation system based on intermediate heat exchange is proposed. The optimum operating parameters of the new system are obtained. The total energy consumption of the distillation columns can be reduced by 38.8%. The water savings of the new system can be reduced by 42.5%. The fixed payback period for the renovated project is about 3.0 years. Abstract: Deepening the energy-saving potential of the distillation process by waste heat recovery is an essential direction in the petrochemical industry. This paper proposes a distillation system of absorption heat pumps based on intermediate heat exchange through waste heat recovery and cascade energy consumption to improve energy efficiency significantly. Firstly, a mathematical model was developed using the numerical simulation software Aspen Plus for the example of a depropanizing column in a gas fractionation system with an annual capacity of 180, 000 ton. Secondly, the optimization of critical parameters, including the material parameters of the intermediate-reboiler and intermediate-condenser and the operational performance of the AHP, is further investigated. The numerical simulation results show that the steam consumption can be decreased by 25% when the pressure in the distillation column is 1.3 MPa, and the heating temperature of the heat pump is 76 ℃. Finally, a complete energy-saving distillation system involving a three-column process has been designed. The effects are significant: 92, 000 ton of steam can be saved annually, corresponding to a reduction of 38.8%; 33, 300 ton of softened water can be saved annually, which equals to a reduction of 42.5%; an economic profit of 5, 429, 000 CNY can be achieved annually, and the fixed investment payback period is only 3 years.